Analisis FTE & RSME Untuk Menentukan Kebutuhan Tenaga Kerja Riset Optimal (Studi Kasus Kantor Mejing PT. Stechoq Robotika Indonesia) - Meilani, Rahmatika Chasania; Hasibuan, Sawarni (Proceeding Mercu Buana Conference on Industrial Engineering, 2021)
In meeting the needs for innovation in the current digital era, PT Stechoq must be able to complete the project according to the set timeline. The high fulfillment of research targets with a limited number of manpower causes the manpower to have to do multiple jobs and work overtime to ensure there are no delays in project completion. The office with the longest working hours at PT Stechoq Robotika Indonesia is the Mejing office with an average working hour of 8.50 hours/day. This study aims to analyze the time and mental workload and calculate the optimal amount of manpower by integrating the FTE & RSME methods. The results showed that the workload of all PT Stechoq research staff, totaling 9 people, was in the excessive workload category. It is proven in the results of calculating the time workload using the FTE method showing a range of 1.47-2.17 which means it is included in the Overload time load category and the results of calculating mental workload using the RSME method have a range of 53.33-93.33 or have an average of 80.74 which means it is included in the category of moderately large mental burden. Then, the calculation results show that the optimal research staff required by the company is 16 manpower. So that an additional manpower of 7 people is needed. With the distribution of additional manpower for Supervisor positions 3 people, for Mechanical Staff positions 2 people, and for Electrical Staff positions 1 person, and for Production Staff positions 1 person.